2010
DOI: 10.1097/ta.0b013e3181d53f81
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Periprosthetic Fractures After Total Knee Arthroplasty

Abstract: Compared with current data in literature, we had a satisfactory outcome in following individualized treatment of periprosthetic fractures after knee joint replacement. Referring to the wide field of treatment options and high rates of complications, periprosthetic femoral fractures around the knee commonly constitute a challenging problem for the treating surgeons and require an adequate analysis of fracture etiology and a corresponding transfer into an individual treatment concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 25 publications
1
55
0
2
Order By: Relevance
“…Für die Behandlung periprothetischer Frakturen des distalen Femurs sind verschiedenste Verfahren beschrieben worden [2,3,4,5,11,16,20,22,25,26]. Die Behandlung undislozierter Frakturen mittels Gipsruhigstellung, Orthese oder Fixateur externe ist in Ausnahmefällen mög-lich, jedoch erlaubt die operative Stabilisation eine unmittelbare Bewegungstherapie und wird daher meist bevorzugt [3,16].…”
Section: Vorbemerkungenunclassified
“…Für die Behandlung periprothetischer Frakturen des distalen Femurs sind verschiedenste Verfahren beschrieben worden [2,3,4,5,11,16,20,22,25,26]. Die Behandlung undislozierter Frakturen mittels Gipsruhigstellung, Orthese oder Fixateur externe ist in Ausnahmefällen mög-lich, jedoch erlaubt die operative Stabilisation eine unmittelbare Bewegungstherapie und wird daher meist bevorzugt [3,16].…”
Section: Vorbemerkungenunclassified
“…Other studies showed that almost 50% of patient with humeral PF had a diagnosis of RA (3). Platzer et al (13) reported the presence of severe osteoporosis or RA in 73% of patients treated for distal femoral PF. The evalutation of implants fixation and the prevention of loosening are essential in order to reduce the risk of PFs.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…3 Indications Surgical treatment goals for periprosthetic fractures around TKA implants include restoration of stability and facilitation of joint motion. Although most fractures can be treated with internal fixation, 4 there are a notable minority of patients for whom additional considerations may limit the effectiveness of internal fixation and increase the benefits of revision total knee arthroplasty as a primary treatment approach.…”
mentioning
confidence: 99%
“…Large osteolytic defects may directly undermine fracture stability or may contribute to implant failure after fracture repair (►Figs. [3][4][5][6]. The adverse bone remodeling in response to aging, metabolic diseases including osteoporosis, or a history of limited weight bearing may also adversely impact the ability to provide adequate stability with an internal fixation construct.…”
mentioning
confidence: 99%